PELATIHAN DESAIN GRAFIS CORELDRAW SEBAGAI UPAYA PEMBERDAYAAN ANAK YATIM DAN DHUAFA BINAAN BAZNAS BEKASI - Supratno, Setyo; Rahmanto, R. Hengki (An-Nizam, 2024)
The lack of practical skills among orphans and economically disadvantaged youth often limits their opportunities for employment or entrepreneurship. To address this issue, a one-day graphic design training program was organized by BAZNAS Bekasi in collaboration with Universitas Islam 45 Bekasi. The program aimed to equip 25 participants with basic graphic design skills using CorelDRAW, focusing on creating business cards, flyers, stickers, calendars, and other print-related products. The training was conducted through a hands-on approach, beginning with an introduction to the software interface, followed by practice using essential tools, and concluding with independent design tasks under expert guidance. Participants demonstrated significant improvements in technical skills, as evidenced by their ability to produce quality designs despite having no prior experience. The program also boosted participants’ confidence and provided them with insights into career opportunities within the creative industry. This initiative effectively empowered participants to achieve economic independence while fostering the development of practical skills aligned with labor market demands.